Concordance between caregiver and child reports of children’s oral health-related quality of life - Wilson-Genderson M, Broder, HL, Phillips C. (Blackwell Synergy, 2007)
This study sought to assess child-caregiver concordance regarding children’s oral health related quality of life (OHRQoL) using the Child Oral Health Impact Profile (COHIP).